RESEARCH INTO PERSONAL VALUES IN TERMS OF QUALITATIVE ANALYSIS OF DOCUMENTS - Dombrovskis, Aivis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This research has emerged from a real-life situation where there was a need to find out for what are the life values and which values are followed by a participant.The study was commissioned in connection with legal proceedings. In this research there is only one participant. The purpose of the study is to explore the categories of personal values and the inherent characteristics of the person revealed in the documents submitted to the study. The study was conducted using a qualitative data-processing method: contentanalysis.The documents analysed in this study consist of three sets of data: telephone text messages, letters and notes and conclusions of psychological studies. A total of eight letters and notes on ten pages have been analysed four hundred and forty-two telephone text messages have been analysed and six psychological investigations conclusions have been analysed on fifteen pages. The conclusions of the psychological investigations where that they were also used as instruments for confirmation of external credibility. The study resulted in individual-specific value categories and external validation of the research has been confirmed.